2014
DOI: 10.1007/s13524-014-0329-2
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Income Volatility and Adult Outcomes

Abstract: Using data linked across generations in the Panel Study of Income Dynamics, I estimate the relationship between exposure to volatile income during childhood and a set of socioeconomic outcomes in adulthood. The empirical framework is an augmented intergenerational income mobility model that includes controls for income volatility. I measure income volatility at the family level in two ways: (1) instability as measured by squared deviations around a family-specific mean; and (2) instability as percentage change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
97
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(104 citation statements)
references
References 79 publications
4
97
3
Order By: Relevance
“…For women, SNAP has been linked to an increase in economic self-sufficiency (Almond et al 2011; Hoynes et al 2015). And finally, higher income during childhood for low-income families has been associated with a range of positive socioeconomic and behavioral outcomes (Akee et al 2015; Duncan et al 2011, 2014; Hardy 2014; Cooper and Stewart 2013). …”
Section: Resultsmentioning
confidence: 99%
“…For women, SNAP has been linked to an increase in economic self-sufficiency (Almond et al 2011; Hoynes et al 2015). And finally, higher income during childhood for low-income families has been associated with a range of positive socioeconomic and behavioral outcomes (Akee et al 2015; Duncan et al 2011, 2014; Hardy 2014; Cooper and Stewart 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Until now, only a few studies have examined variation in childhood family income and its association with health and social outcomes 10–12. These studies have found unfavourable relationships between childhood family income instability and children's educational attainment,10 11 development12 and behavioural problems 12. These studies have mostly focused on income fluctuation in general, but have also suggested that income fluctuations may be particularly harmful among low-income families.…”
Section: Introductionmentioning
confidence: 99%
“…Three recent studies demonstrated negative associations between income volatility and both adolescent and adult school outcomes (Gennetian et al, , ; Hardy, ). Two of these studies (Gennetian et al, ; Hardy, ) used nationally representative data and showed that the adverse effects are larger for lower income and non‐White adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Economic disadvantage is highly stratified by race and ethnicity in the United States, with Hispanic and non‐Hispanic Black families facing higher poverty rates, lower average income and wealth, and higher rates of material hardship than non‐Hispanic White families (McKernan, Ratcliffe, Steuerle, & Zhang, ; Neckerman, Garfinkel, Teitler, Waldfogel, & Wimer, ; Semega, Fontenot, & Kollar, ). Recently, research in economics and sociology has drawn attention to income volatility as a distinct form of economic disadvantage with implications for child and adult well‐being (Gennetian, Rodrigues, Hill, & Morris, ; Gennetian, Wolf, Hill, & Morris, ; Hardy, ; Western, Bloome, Sosnaud, & Tach, , ), but we know little about how income volatility differs by race and ethnicity.…”
mentioning
confidence: 99%
See 1 more Smart Citation